LEADERSHIP STYLES AND RESILIENCE AS CORRELATES OF EMPLOYEE COMMITMENT AMONG MILITARY HEALTH WORKERS IN ENUGU AND ONITSHA, SOUTHEAST NIGERIA - EZEH, Leonard Nneamaka; OLAWALE, Kehinde (Socialscientia: Journal of Social Sciences and Humanities, 2018)
This study investigated leadership styles and resilience as predictors of employee commitment among Military health workers in Enugu, Enugu state and Onitsha, Anambra state, Southeast, Nigeria. Two hundred and eighteen (218) participants made up of 142 males (65.15%) and 76 females (30.73%) were selected using convenience sampling technique. Their ages ranged from 22 to 69 with the mean age of 39.5 and standard deviation of 2.36. Three instruments were adopted to gather data for the study, namely: a 21 item Multifactor Leadership Questionnaire (MLQ) developed by Bass and Avolio (2004), a 26 item Resilience scale (RS) developed by Wagnild and Young (1993), and an 18 item Organizational Commitment Questionnaire (OCQ) developed by Meyer and Allen (1993). Pearson’s product moment correlation was used as a statistical tool to test three hypotheses. The results of the study revealed that transformational leadership style significantly and positively correlated with employee commitment among Military health workers. Also, findings revealed that transactional leadership significantly and positively correlated with employee commitment of Military health workers. Furthermore, results indicated that resilience significantly and positively correlated with employee commitment among Military health workers. The study recommended that Military organization should adopt transformation and transactional leadership styles to improve the resilience of their health workers to gain their full commitment to the organization, while scholarly studies are called upon to replicate the study with larger group samples and in other sectors of economy to further validate its generalizability.